2001
DOI: 10.1128/aac.45.2.540-545.2001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Dose Pharmacokinetics and Tolerability of Gemifloxacin Administered Orally to Healthy Volunteers

Abstract: Gemifloxacin mesylate (SB-265805-S, LB-20304a) is a potent, novel fluoroquinolone agent with a broad spectrum of antibacterial activity. The pharmacokinetics and tolerability of oral gemifloxacin were characterized in two parallel group studies in healthy male volunteers after doses of 160, 320, 480, and 640 mg once daily for 7 days. Multiple serum or plasma and urine samples were collected on days 1 and 7 and were analyzed for gemifloxacin by high-performance liquid chromatography (HPLC)-fluorescence (study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…The t 1/2 was determined to be 17.6 to 19.8 h. The Ae 24 accounted for 37 to 58% of the drug. The range of renal elimination for nemonoxacin falls into the range of data reported for other quinolones (20 to 30% for gemifloxacin, 80% for levofloxacin, 20% for moxifloxacin, and 30 to 50% for garenoxacin) (1,2,5,11,21,30). Metabolism studies completed to date indicate that no metabolite or a minor metabolite (less than 5%) of nemonoxacin was formed either in vitro or ex vivo (reference 7 and unpublished data).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The t 1/2 was determined to be 17.6 to 19.8 h. The Ae 24 accounted for 37 to 58% of the drug. The range of renal elimination for nemonoxacin falls into the range of data reported for other quinolones (20 to 30% for gemifloxacin, 80% for levofloxacin, 20% for moxifloxacin, and 30 to 50% for garenoxacin) (1,2,5,11,21,30). Metabolism studies completed to date indicate that no metabolite or a minor metabolite (less than 5%) of nemonoxacin was formed either in vitro or ex vivo (reference 7 and unpublished data).…”
Section: Discussionmentioning
confidence: 63%
“…In the early phase Ia study, plasma binding of nemonoxacin was shown to be about 16% (18). When administered at a dose of 500 mg or higher, the free plasma concentration of nemonoxacin was well above the MIC 90 s for a wide spectrum of Gram-positive, Gram-negative, and atypical pathogens for the full 24-h dosing interval (1,4). Data from a variety of in vitro, animal, and human studies have suggested that the bactericidal activity of FQs is rapid and concentration dependent (10,20,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…A method was developed by Doyle et al 15 for the determination of gemifloxacin in human plasma using liquid chromatography-tandem mass spectrometry. Allen et al 16 have quantified concentrations of gemifloxacin in serum and urine by a reversedphase liquid chromatography (LC) method with fluorescence detection (SmithKline Beecham, unpublished data).…”
Section: Introductionmentioning
confidence: 98%
“…The adverse reaction profile is similar to that of older members of this class (3,24). Previous studies have shown that gemifloxacin displays a favorable plasma pharmacokinetic (PK) profile allowing a once-daily dosing regimen (1,2).…”
mentioning
confidence: 61%